Effect of Dietary Vitamin C Ascorbic Acid on the Growth Performance and Immune Response of Betok Anabas testudineus Bloch - Sunarto, .; Suriansyah, .; Sabariah, . (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
Vitamin C has a function for increasing normal growth, preventing bone annomaly for seed health or reducing stress, accelerating wound recovery and improving immune system against bacterial infection. Enhancement of immune response using immunostimulant had been proven in aquaculture. One of the immunostimulant that had been examined in several fish species was vitamin C. However, the immunostimulatory effect of vitamin C on betok remains to be proven. This study was performed to know the effect of feeding fish by diets containing vitamin C in form of ascorbic acid on growth and immune response of betok in term of stress adaptation. Concentrations of vitamin C tested were 0 (control), 125 mg, 250 mg and 375 mg/kg diet. The results show that supplementation of vitamin C in diet can increase daily growth rate and feed efficiency of betok. Daily growth rate of treated fishes (1.37-1.49%) were higher than that of control (1.14%). Feeding efficiency was also higher in treated fishes (39.73-48.07%) compared to that of control (33.73%). There was no significantly difference in survival rate of treated fish (93.33-96.67%) and control (93.33%). Survival rate of fish reared at 15oC as a stress test was also examined. Results showed that survival rate of fish increases by increasing the level of vitamin C in diet. Number of fish died in stress test was 10 in control, 7 fish in 125 mg/kg, 5 fish in 250 mg/kg and 3 fish in 375 mg/kg. Thus, inclusion of vitamin C in diet improved ability of fish to adapt to an extreme environment condition. Keywords: Vitamin C, ascorbic acid, growth, immune response, Anabas testudineus ABSTRAK Vitamin C berfungsi untuk meningkatkan pertumbuhan normal, mencegah kelainan bentuk tulang untuk kesehatan benih atau mengurangi stress, mempercepat penyembuhan luka dan meningkatkan pertahanan atau kekebalan tubuh melawan infeksi bakteri. Peningkatan respon imun dengan pemberian imunostimulan telah dibuktikan dalam akuakultur. Salah satu immunostimulan yang telah diuji pada beberapa spesies ikan adalah vitamin C. Namun demikian, pengaruh imunostimulatori vitamin C pada ikan betok belum diteliti. Penelitian ini dilakukan untuk mengetahui efek pemberian pakan yang mengandung vitamin C dalam bentuk ascorbic acid terhadap pertumbuhan dan respons imun dalam arti daya tahan terhadap stres pada ikan betok. Dosis vitamin C adalah 0 (kontrol), 125 mg, 250 mg dan 375 mg/kg pakan. Hasil penelitian menunjukkan bahwa penambahan vitamin C dalam pakan dapat meningkatkan laju pertumbuhan harian dan efisiensi pakan pada ikan betok. Laju pertumbuhan harian pada ikan perlakuan (39.73-48.07%) lebih tinggi daripada ikan (33.73%). Kelangsungan hidup ikan tidak berbeda antara perlakuan (93.33-96.67%) dan kontrol (93.33%). Kelangsungan hidup ikan yang dipelihara pada suhu 15oC sebagai uji stress as a stress juga diamati. Hasil penelitian menunjukkan bahwa kelangsungan hidup ikan meningkat dengan meningkatnya kadar C dalam pakan. Jumlah ikan yang mati dalam uji stres adalah 10 pada kontrol, 7 pada perlakuan 125 mg/kg, 5 ekor pada perlakuan 250 mg/kg dan 3 ekor pada perlakuan 375 mg/kg. Dengan demikian, penambahan vitamin C dalam pakan meningkatkan kemampuan ikan beradaptasi terhadap kondisi lingkungan esktrim. Kata kunci : Vitamin C, ascorbic acid, pertumbuhan, respons imun, Anabas testudineus